Analisis Laju Erosi Dan Upaya Penanggulangannya di DAS Bolapapu - Natsir, Muhammad; Hasanah, Uswah; Monde, Anthon (Mitra Sains, 2023)
This research aims to determine the factors that cause erosion, measure the level and how to overcome the dangers of erosion in the Bolapapu watershed. This research was conducted in the Bolapapu watershed which is located in the middle of the Miu sub-watershed and is located in Kulawi District, Sigi Regency, Central Sulawesi Province. The results of the research show that in various forms of land use using plant management methods (C) and conservation techniques, namely soil management (P), there are several things that can be concluded: (1) changes in plant management factors on each land unit can prevent the level of danger of erosion and can increase land productivity; (2) conservation measures, namely soil management (P), can change the physical shape of the length and slope of the slope and inhibit the rate of runoff; (3) in land rehabilitation efforts using plant and soil management methods in relation to erosivity which can change the physical form of erodibility; (4) land rehabilitation planning in the Bolapapu watershed can not only reduce the level of erosion hazard or increase land productivity, but can improve the economic conditions of the community through plant management. economically valuable actions through conservation techniques.